2014
DOI: 10.1002/jip.1421
|View full text |Cite
|
Sign up to set email alerts
|

Tall Tales Across Time: Narrative Analysis of True and False Allegations

Abstract: Little consensus exists regarding how the details of truthful and false allegations of traumatic victimisation may change over short and long time intervals, yet this cue is utilised in the assessment of witness, victim and suspect credibility. The present study involved a narrative analysis of the details written within 147 sets of allegation statements across both short-term (~3 months) and long-term (~6 months) intervals. Overall results indicated that true allegations contained more consistent details, omi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…This is especially salient in individuals that suffered from repeated victimization. Thus, the memory concerning the occurrence of the victimization tends to be more precise than the memory for its specific course: participants remember the victimization, but may not be able to correctly recall if it happened during childhood, adolescence or adulthood (Hardt & Rutter, ; Peace et al ., ; Quas, Alexander, Goodman, Ghetti, Edelstein & Redlich, ; van Giezen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially salient in individuals that suffered from repeated victimization. Thus, the memory concerning the occurrence of the victimization tends to be more precise than the memory for its specific course: participants remember the victimization, but may not be able to correctly recall if it happened during childhood, adolescence or adulthood (Hardt & Rutter, ; Peace et al ., ; Quas, Alexander, Goodman, Ghetti, Edelstein & Redlich, ; van Giezen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that there may be a trend to increase the number of victimization reported over assessments. This may be due to underreport in initial assessments, and the effect of rehearsal (Epstein & Bottoms, ; Ghetti, Goodman, Eisen, Qin & Davis, ; Kremers et al ., ; Kringsley, Gallagher, Weathers, Kulter & Kaloupek, ; Odinot, Wolters & van Giezen, ; Peace, Shudra, Forrester, Kasper, Harder & Porter, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, as many potential jurors believe that false accusations of abuse by children are common (McGee et al, 2011), lawyers can use this belief to structure their argument and questioning. In addition, deviations from the 'ideal victim' of abuse can be used to assert that such abuse did not happen, or was consensual (Peace et al, 2015), as lawyers may be aware that jurors will have trouble 'anchoring' the events being described in court to socially constructed ideas of how child abuse occurs. Indeed, as the presence of such stereotypes have been found to influence mock-juror verdicts more than case facts (Goodman & Melinder, 2007) it seems logical that lawyers will exploit victim and perpetrator stereotypes for juror to anchor and understand the events in court in relation to a socially shared and accepted script (O'Connor, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Social representations may further create stereotypes of 'ideal' victims and 'ideal' defendants (Lindholm & Cederborg, 2016). Any deviations from these ideals may be highlighted by lawyers seeking to suggest that the abuse may not have occurred (Peace, Shudra, Forrester, Kasper, Harder, & Porter, 2015).…”
Section: How Do Lawyers Construct Children's Narratives In Court?mentioning
confidence: 99%
See 1 more Smart Citation